Anaplasma phagocytophilum Inhibits Apoptosis and Promotes Cytoskeleton Rearrangement for Infection of Tick Cells - Ayllón, Nieves (2013)
Anaplasma phagocytophilum causes human granulocytic anaplasmosis. Infection with this zoonotic pathogen affects gene expression in both the vertebrate host and the tick vector, Ixodes scapularis. Here, we identified new genes, including spectrin alpha chain or alpha-fodrin (CG8) and voltage-dependent anion-selective channel or mitochondrial porin (T2), that are involved in A. phagocytophilum infection/multiplication and the tick cell response to infection. The pathogen downregulated the expression of CG8 in tick salivary glands and T2 in both the gut and salivary glands to inhibit apoptosis as a mechanism to subvert host cell defenses and increase infection. In the gut, the tick response to infection through CG8 upregulation was used by the pathogen to increase infection due to the cytoskeleton rearrangement that is required for pathogen infection. These results increase our understanding of the role of tick genes during A. phagocytophilum infection and multiplication and demonstrate that the pathogen uses similar strategies to establish infection in both vertebrate and invertebrate hosts.